Want to be happy? Head for Vanuatu - Abd Razak, Dzulkifli (2006)
GIVEN the prospect of endless violence worldwide, it is interesting to understand the true meaning of "happiness" to the world. Until lately, there was no way of telling. Now it is possible by using the Happy Planet Index (HPI). This is an innovative attempt to measure a country's level of happiness compared to the rest of the world. Drawn up by the National Economics Foundation (NEF), a British thinktank, it claimed to be the first ever index to combine environmental impact with wellbeing. Andrew Simms, the foundation's policy director, was quoted as saying the index "addresses the relative success or failure of countries in giving their citizens a good life while respecting the environmental resource limits on which all our lives depend".